THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF TWO STAY TWO STRAY (TSTS) AND INDEX CARD MATCH ON STUDENTS MATHEMATICS LEARNING ACHIEVEMENT IN GRADE VII - Tri Widiastuti; Widayati Widayati (Universitas Ahmad Dahlan, 2018)
The low student learning outcomes are influenced by several factors, one of which the model used in the less varied learning of mathematics is still centered on the teacher. This study aims to determine more effective learning between mathematics learning using cooperative learning model type two to stay two strays with learning mathematics with a cooperative learning model type index card match to students' mathematics learning outcomes. This study population was all seven grade students of State Islamic Junior High School 7 Sleman (MTs Negeri 7 Sleman) regency Academic Year 2016/2017, which consists of 5 classes. The sampling technique using a random sampling technique and selected class VII A as an experimental I class and class VII C as an experimental II class. The data was collected using the test method—tests using instrument validity and reliability. Data analysis techniques used for the analysis include the prerequisite test, normality test, and homogeneity test. Analysis of data used hypothesis testing. Based on mathematics learning result obtained that 1) and which means . This means that there is a difference in learning outcomes between learning mathematics using cooperative learning model type two stay two strays with mathematics learning using a cooperative learning model type index card match of seven grade students of MTs Negeri 7 Sleman in even semester regency Academic Year 2016/2017. 2) and which means . This shows that the learning of mathematics with cooperative learning model type two stay two strays are more effective than the learning of mathematics using cooperative learning model type index card match towards mathematics learning outcomes in seven grade students of MTs Negeri 7 Sleman in even semester regency Academic Year 2016/2017.